Mineral Occurrences in the Area of the King Tut Mine, La Rioja province, Argentina - Sangster, Alan L. (2002)
Fil: Sangster, Alan L. Servicio Geológico Minero Argentino. Instituto de Geología y Recursos Minerales; Argentina.